Creating Web Portals for a Multi-Type Library System: The Use of Open Source Code in the Chicago Library System. - Hepburn, Peter; Kayiwa, Francis (Public Services Quarterly, 2003)
Institutions of higher education are among the most prominent proponents of portals. A group of resident librarians at the University of Illinois at Chicago (UIC) has targeted a larger audience by creating a customized Web portal to be used by library patrons throughout the Chicago area, whether they are academic, public, school or special library users. The portal project has raised issues of maintenance and administration, as well as those of the collaborative process between libraries in a system.